2018
DOI: 10.3390/w10070948
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Perched Epikarst Aquifer and Unsaturated Soil Cover in the Initiation of Shallow Landslides in Pyroclastic Soils

Abstract: A physically based mathematical model of the slope of Cervinara (southern Italy), which is characterized by a shallow pyroclastic soil cover laying upon a limestone fractured bedrock, has been developed. Previous and current ongoing monitoring suggested that leakage through the soil-bedrock interface occurred, with leaking water temporarily stored in a perched aquifer located in the upper part of the fractured limestone (epikarst). This aquifer supplied several springs, and recharge to the deeper groundwater c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…However, the soil depth involved in a shallow landslide (the most prominent landslide type globally) is typically 1-2 m below the surface (Fiorillo et al 2001;Greco et al 2018), which is much thicker than the soil depth currently directly measured by remote sensing techniques, and in many cases overlaps with the root penetration depth. Such zone is influenced by antecedent precipitation, soil texture, vegetation, and therefore a clear relationship with nearsurface soil moisture may be difficult to find.…”
Section: Landslidesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the soil depth involved in a shallow landslide (the most prominent landslide type globally) is typically 1-2 m below the surface (Fiorillo et al 2001;Greco et al 2018), which is much thicker than the soil depth currently directly measured by remote sensing techniques, and in many cases overlaps with the root penetration depth. Such zone is influenced by antecedent precipitation, soil texture, vegetation, and therefore a clear relationship with nearsurface soil moisture may be difficult to find.…”
Section: Landslidesmentioning
confidence: 99%
“…in the order of 10 −5 -10 −4 m s −1 for the ashes, and even higher for the pumices). The soil-bedrock interface is pervious, and the leakage supplies both shallow and deep groundwater circulation (Allocca et al 2014;Greco et al 2018). Hence, the soil cover has high water retention capacity and allows for rapid infiltration and drainage processes.…”
Section: Campaniamentioning
confidence: 99%
“…Rainfall is one of the main factors that trigger landslides [1]. In the past two decades, research on rainfall-induced soil landslides has been gaining popularity [2][3][4][5][6], but research on rock landslides is less reported [1,[7][8][9][10][11][12]. According to available statistical data, more than 90% of rock slope failures are related to fluid hydraulic conduction [13].…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic nature of subsurface hydrology depends on the complex interactions among precipitation inputs, physical properties and heterogeneity of soils and bedrock, local geomorphology, and vegetation and associated biomass. These factors influence the timing of landslides with respect to precipitation inputs and antecedent soil moisture [14][15][16][17], the mass and mode of failure [18], and the extent of runout or transformation of landslides into debris flows [19].Both the infiltration of rainwater and snowmelt and bedrock exfiltration provide the local trigger of these landslides, while drainage and evapotranspiration tend to stabilize hillslopes by rerouting and removing subsurface water. Subsurface hydrology is strongly affected by preferential flow within the soil, substrate topography, and exfiltration from fractures in bedrock [2,13,18,[20][21][22]; the overall regolith moisture regime and recharge rates are influenced by evapotranspiration, soil development processes, soil water-groundwater interactions, and landform aspect and shape [14,16,[23][24][25].…”
mentioning
confidence: 99%
“…This dynamic nature of subsurface hydrology depends on the complex interactions among precipitation inputs, physical properties and heterogeneity of soils and bedrock, local geomorphology, and vegetation and associated biomass. These factors influence the timing of landslides with respect to precipitation inputs and antecedent soil moisture [14][15][16][17], the mass and mode of failure [18], and the extent of runout or transformation of landslides into debris flows [19].…”
mentioning
confidence: 99%